Mr. Putter & Tabby : Walk the dog - Rylant, Cynthia; Howard, Arthur (San Diego : Harcourt Brace, 2008)
When their neighbor Mrs. Teaberry hurts her foot, Mr. Putter and his cat Tabby agree to walk her dog for a week, not knowing what they are in for.
Elem. School Library Collection
School Library Journal
School Library Journal starred
Booklist, August 1997
Elem. School Library Collection, June 2000
Horn Book, November 2004
Keywords: Dogs -- Juvenile fiction; Cats -- Fiction; Dogs -- Fiction; Old age -- Fiction; Cats -- Fiction; Dogs -- Fiction; Old age -- Fiction